Megalithic Landscapes and Social Memory in South India: An Archaeological Interpretation (MINDEN Journal of History and Archaeology, 2026)
Megalithic monuments constitute one of the most prominent archaeological features of the Iron Age in South India, yet they have often been interpreted primarily through typological classification and chronological sequencing. This article advances an alternative, interpretive framework by examining megalithic landscapes as materialized practices of social memory. Drawing on archaeological evidence from across South India, the study situates burial monuments within their spatial contexts to analyse how durability, visibility, monumentality, and long-term reuse enabled communities to anchor remembrance within lived landscapes. Rather than treating megaliths as static funerary structures, the article argues that they functioned as active mnemonic devices through which ancestry, social identity, and hierarchy were negotiated and reproduced over time. Variability in burial architecture and assemblages is interpreted not only as cultural or environmental variation but as differentiated modes of remembering shaped by social relations and historical trajectories. Through a comparative engagement with megalithic traditions beyond South India, the study suggests that while monumentality reflects a broader human strategy of materializing memory, its meanings are locally configured. Methodologically, the article highlights the analytical value of integrating social memory with landscape archaeology for interpreting protohistoric societies where textual sources are limited. By foregrounding memory-making as a spatial and material process, the study contributes a theoretically transferable approach to the archaeology of mortuary landscapes.Keywords: Megaliths; Social Memory; Landscape Archaeology; Protohistory; Mortuary Practices; South India